PHYSIOLOGICAL ADAPTATIONS TO INTERMITTENT FASTING: ENDOCRINE AND METABOLIC RESPONSES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review aims to explore the physiological adaptations resulting from intermittent fasting, and to understand the endocrine and metabolic responses. It also highlights the important role of intermittent fasting in modulating hormone secretion, improving metabolic efficiency, and promoting long-term overall health. The study was conducted using an analytical approach based on scientific studies on intermittent fasting and its effects on the body in particular and on health in general. The study focused on hormonal responses, including insulin, glucagon, cortisol, thyroid hormones, and growth hormone, along with key metabolic processes such as ketogenesis, autophagy, and mitochondrial adaptation. Review of previous research found that intermittent fasting lowers insulin levels and enhances glucagon secretion, supporting a metabolic shift toward fat oxidation. Short-term increases in cortisol are stabilized during fasting, and thyroid hormone metabolism regulates adaptive metabolism. Growth hormone levels rise during fasting, while insulin-like growth factor-1 levels decline, promoting autophagy. Intermittent fasting also enhances mitochondrial efficiency and reduces oxidative stress. The article proved that Intermittent fasting has profound physiological effects by recalibrating hormonal pathways and improving metabolic processes. These effects contribute to improved glucose control, lipid metabolism, and cellular plasticity. Clinical research supports the therapeutic potential of intermittent fasting in metabolic conditions, cardiovascular disease, and neurodegeneration. Further long-term clinical studies are recommended to confirm these findings.